Aplikasi Android untuk Mencari Harga Tiket Pesawat Termurah dari Beberapa Situs Travel di Indonesia - Bobby Irawan; Henry Novianus Palit; Justinus Andjarwirawan (Jurnal Infra, 2019)
Travel sites in Indonesia offer varied flight ticket prices. So, to find a cheap price becomes difficult, consumers must open every site or application from a travel site to compare the ticket price each site offered. This takes a lot of time, and sometime when you find the right price and want to order it, the ticket sold out. Therefore, an application is needed to search and compare prices from each travel sites. Application was made to do the comparison of price that each travel sites offered. To do a comparison, a server is needed to retrieve each price and details of flights on each travel site. After that, the process continue to processing all data and displayed it to the application.Based on the result of test that been done on program, program managed to collecting, processing, and showing price as well as flight information from travel sites.